DYNAMICS OF DIGITAL MARKETS - Thorhauge, Anne Mette; Yuan, Jingyan Elaine; Ørmen, Jacob; Gregersen, Andreas; Vonderau, Patrick (AoIR Selected Papers of Internet Research, 2021)
The focus of this panel is the material, organizational, and cultural conditions of digital markets. While the notion of economy refers to the more general production, distribution and allocation in society, the idea of markets represents specific contexts of economic exchange typical of capitalist economies (Carruthers & Babb, 2013). A more elaborate understanding of digital markets and their relationships with digital platforms can expand our understanding of the economic implications that specific types of platform architectures have at the level of economic interaction. The discussion takes as a starting point perspectives from economic sociology that emphasize how markets are embedded into broader social and societal structures (Granovetter, 2017) and conditioned upon cultural norms and conventions (Beckert, 2009). In addition, the panel is informed by the way economic sociology and STS have approached the material conditions of markets (Garcia-Parpet, 2007; MacKenzie, 2018) and the way these conditions frame and transform power relations and interaction patterns on specific markets. The panel consists of four papers that approach this issue from a range of perspectives: The relationship between platform architectures, open market strategies and the formation of ‘commodity money’ in the case of Steam, the relationship between platforms, markets, and state regulation in the case of Alibaba, the role of narratives, imagined futures, and collective action that frame patterns of buying and selling in global stock markets in the case of Gamestop shares and, finally, how the online engagement industry is organized in practice in the case of “click farms”.